2017
DOI: 10.1080/10749357.2017.1285746
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of mechanisms of gait speed change post-stroke. Part 1: spatiotemporal parameters and asymmetry ratios

Abstract: Background In walking rehabilitation trials, self-selected walking speed has emerged as the dominant outcome measure to assess walking ability. However, this measure cannot differentiate between recovery of impaired movement and compensation strategies. Spatiotemporal variables and asymmetry ratios are frequently used to quantify gait deviations and are hypothesized markers of recovery. Objectives The purpose of this review is to investigate spatiotemporal variables and asymmetry ratios as mechanistic recove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(67 citation statements)
references
References 83 publications
1
65
0
1
Order By: Relevance
“…Three systematic reviews (Stergiou et al, ; White‐Lewis et al, ; Wonsetler & Bowden, ) examined the effect of hippotherapy or THR on adults following stroke, however, this constituted only three unique studies. Motor impairment in the lower limbs (Stergiou et al, ; White‐Lewis et al, ), gait velocity (White‐Lewis et al, ), step length asymmetry (White‐Lewis et al, ; Wonsetler & Bowden, ), and quality of life (White‐Lewis et al, ) demonstrated statistically significant improvements while balance (White‐Lewis et al, ), ambulation (White‐Lewis et al, ), and cadence did not (White‐Lewis et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Three systematic reviews (Stergiou et al, ; White‐Lewis et al, ; Wonsetler & Bowden, ) examined the effect of hippotherapy or THR on adults following stroke, however, this constituted only three unique studies. Motor impairment in the lower limbs (Stergiou et al, ; White‐Lewis et al, ), gait velocity (White‐Lewis et al, ), step length asymmetry (White‐Lewis et al, ; Wonsetler & Bowden, ), and quality of life (White‐Lewis et al, ) demonstrated statistically significant improvements while balance (White‐Lewis et al, ), ambulation (White‐Lewis et al, ), and cadence did not (White‐Lewis et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Variability was expressed by standard deviation/mean ×100% to indicate the consistency of gait Scientific RepoRtS | (2020) 10:1201 | https://doi.org/10.1038/s41598-020-58098-0 www.nature.com/scientificreports www.nature.com/scientificreports/ pattern 44 . Asymmetry ratio was quantified by the percentage as follows: paretic side/non-paretic side ×100%, with step length indicating for spatial parameters and step time for temporal 45 . The averaged value of 3 trials were used for data analysis.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…This was clearly demonstrated by another systematic review that assessed the effectiveness of cardiovascular conditioning on comfortable gait speed. This meta‐analysis showed a small increase of 0.08 m/s, but the average gait speed at the end was 0.72 m/s, which was responsible for the improvement of walking speed from moderate to mild [27]. Moreover, changes ranged from 0.10 to 0.20 m/s were demonstrated to be minimal clinically important for difference in comfortable gait speed across multiple patients with disease [30].…”
Section: Discussionmentioning
confidence: 74%